The Recognition And Enforcement Of International Arbitration Awards In Indonesia Under Law No. 30 Of 1999 And The 1958 New York Convention - Ario Titisan (Journal of Law, Social Science, and Management Review, 2026)
Indonesia ratified the 1958 New York Convention through Presidential Decree Number 34 of 1981, thus having an international obligation to recognize and enforce foreign arbitral awards. Further regulations are contained in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, which confirms that the execution of international arbitral awards. The formulation of the problem 1. How is the recognition and enforcement of international arbitral awards in Indonesia according to Law No. 30 of 1999 and the 1958 New York Convention? The 1958 New York Convention regulates the mechanism for resolving international business disputes through arbitration by emphasizing the principle of recognition and enforcement of foreign arbitral awards broadly, the principle of finality and binding, and limitations on the grounds for refusing to execute arbitral awards. This convention provides legal certainty and efficiency in resolving cross-border disputes, while encouraging the use of arbitration as a neutral and effective alternative dispute resolution in international trade practices. The recognition and enforcement of international arbitral awards in Indonesia have been accommodated through Law No. Law No. 30 of 1999 adopted the principles of the 1958 New York Convention, specifically regarding the obligation to recognize and enforce foreign arbitral awards through the exequatur mechanism by the Supreme Court.